2020
DOI: 10.1177/1073274820945984
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Biology is King: Secondary Tumors of the Thyroid From 2 Medical Centers in China

Abstract: Background: We studied the clinical characteristics, diagnosis, treatment, and prognosis of secondary tumors of the thyroid (STTs) and analyzed this rare phenomenon based on our clinical experience. Methods: We reviewed 16 000 malignant thyroid tumors diagnosed at 2 medical centers in China from 1978 to 2018, including 55 patients with STTs. Results: The most frequent primary tumor sites included lung (21.8%), gastrointestinal (18.2%), breast (14.5%), and kidney (12.7%). The median age at STT diagnosis was 56 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…9 In contrast, according to the literature review, CLND (central lymph node dissection) is not the suggested procedure since the rate of lymph node metastasis in patients treated with CLND accounts for just 3%. 3,9 In the present case, a quick and reliable preoperative diagnosis was provided by fine-needle aspiration cytology, performed in accordance with the literature 10,11 .…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…9 In contrast, according to the literature review, CLND (central lymph node dissection) is not the suggested procedure since the rate of lymph node metastasis in patients treated with CLND accounts for just 3%. 3,9 In the present case, a quick and reliable preoperative diagnosis was provided by fine-needle aspiration cytology, performed in accordance with the literature 10,11 .…”
Section: Discussionmentioning
confidence: 61%
“…Dysphonia, dysphagia, hemoptysis, and stridor are among the most common signs in symptomatic patients; anyway, the lack of data in the literature complicates the evaluation of the incidence of symptomatology. 8 The percentage of patients presenting with thyroid metastasis, in need of tracheotomy due to dyspnea accounts for 3.6% 3 ; on the other hand, according to the literature, as many as 10% of patients die from disorders related to tracheal compression. 9 Because of the aggressive nature of the tumor, many of the patients who have been diagnosed with thyroid metastases are often treated with palliative intent.…”
Section: Introductionmentioning
confidence: 99%
“…Among 30 patients, 16 were treated with chemotherapy, and 75% of them were clinically stable during follow-up (Table 1 ). It is believed that the biological behavior of primary cancer might be the primary influence on the prognosis of patients with TM[ 2 ]. Thus, therapeutic choices for TM patients should be determined individually and with multidisciplinary board discussion.…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis to the thyroid gland (TM) is uncommon, accounting for approximately 1.4% to 3% of all thyroid malignancies[ 1 ]. It was reported that metastases mostly arise from the lung (21.8%), followed by the gastrointestinal tract (18.2%), breast (14.5%), and kidney (12.7%), in a recent Chinese study[ 2 ]. Patients with TM usually present with symptoms of thyroid nodules, thyroiditis or neck swelling, dysphagia, dysphonia, and cough[ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various molecular markers should be immunohistochemically evaluated to further determine the origin of the cancer cells. The main immune markers used to differentiate thyroid-metastatic carcinoma from primary thyroid carcinoma are thyroglobulin (TG), thyroid transcription factor 1 (TTF-1), Cdx-2, CK7, and CK20 (6,25). Primary lesions are typically TG and TTF-1-positive, whereas metastatic lesions are typically negative for these markers.…”
Section: Discussionmentioning
confidence: 99%